2018
DOI: 10.1016/j.ejogrb.2018.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Gender and preterm birth: Is male fetal gender a clinically important risk factor for preterm birth in high-risk women?

Abstract: In this cohort, 14.5% of women (363/2505) delivered before 37 weeks. Pregnant women were stratified by fetal gender and were comparable for referral risk factors and demographic characteristics. There was no significant association between fetal gender and incidence of miscarriage less than 24 weeks (RR 1.17, 95% CI 0.65-2.10, p = 0.607), or preterm births 24 to 37 weeks RR 1.07 (95% CI 0.82-1.40, p = 0.383). Furthermore, analysis by gestational band [<28 RR 0.91 (95% CI 0.60-1.37, p = 0.647), <34 RR 1.18 (95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 13 publications
5
11
0
1
Order By: Relevance
“…We found no statistically significant association between the gender of neonates and LPT delivery. This was in agreement with Teoh et al [18] However, several earlier studies [19][20][21][22] reported an increased risk of preterm delivery associated with male fetus. Wilms et al [21] suggested an effect of maternal race on the association between gender and preterm delivery.…”
Section: Discussionsupporting
confidence: 92%
“…We found no statistically significant association between the gender of neonates and LPT delivery. This was in agreement with Teoh et al [18] However, several earlier studies [19][20][21][22] reported an increased risk of preterm delivery associated with male fetus. Wilms et al [21] suggested an effect of maternal race on the association between gender and preterm delivery.…”
Section: Discussionsupporting
confidence: 92%
“…Sex of the child had no any risks for preterm births. This was in line with another study who also showed no signi cant association between sex of the child and preterm births [50]. However, several studies have linked male babies with preterm births [51][52][53].…”
Section: Discussionsupporting
confidence: 90%
“…Sex of the child had no any risks for preterm births. This was in line with another study who also showed no significant association between sex of the child and preterm births [43]. However, several studies have linked male babies with preterm births [44][45][46].…”
Section: Discussionsupporting
confidence: 90%